Data Resource Profile: ECHILD only-children and siblings (ECHILD-oCSib): a national cohort of linked health, education and social care data on mothers and children in England - Feng, Qi; Ireland, Georgina; Gilbert, Ruth; Harron, Katie (International Journal of Population Data Science, 2024)
Introduction Sibling dynamics play a crucial role in individual development, health and wellbeing. We established a national birth cohort using administrative health, education and social care data in England featuring clusters of mothers and their children (mothers and only-children, MoC; and mothers and siblings, MSib). Methods From 13.6 million mother-baby pairs from births between April 1997 and January 2022 captured in Hospital Episode Statistics in England, we identified MoC and MSib clusters by identifying livebirths linked to the same mother. We compared only-children and children with siblings, by ethnicity, sociodemographic variables, and birth characteristics. We calculated birth intervals for children with siblings. Results We identified 4,086,648 MoC and 3,957,856 MSib clusters. Compared with only-children, children with siblings were more likely to be Asian, live in more deprived areas, and have younger mothers, but were less likely to be overdue births (>=42 weeks), or to have very low birth weight (< 1500g). Children with siblings were also less likely to have been admitted to special neonatal care after birth compared to only-children. Among the MSib clusters, sibship sizes varied between 2 and 15, with a mean of 2.4 children per mother. The median birth interval was 3.0 years. Conclusion This national cohort ECHILD-oCSib of 4.1 million MoC and 4.0 million MSib clusters in England is an important resource for investigating the effects of maternal exposures, sibling dynamics and their interplay on individual development, health and wellbeing. Potential sources of bias should be considered in analyses of these data.